2016
DOI: 10.1016/j.jvs.2015.08.108
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocker use is associated with lower stroke and death after carotid artery stenting

Abstract: Background Proper selection of patients for carotid artery stenting (CAS) remains controversial despite multiple controlled trials. This relates in part to differences in interpretation of the relative importance of myocardial vs stroke complications after the procedure by different specialties and a lack of granular clinical data to analyze outcomes outside the large clinical trials. The objective of this study was to assess the effect of preoperative medications, procedure parameters, and patient characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…We insure that all our patients are on statin and aspirin as well as β-blockers and for CAS dual antiplatelet agents is mandatory. 15,16 Statins have been shown to be protective for mortality following CEA and CAS in previous studies; similarly in this study, statins have shown 71% reduction in mortality. 16,17 We patch all our CEA under EEG and evoked potential monitoring with selective shunting.…”
Section: Discussionsupporting
confidence: 81%
“…We insure that all our patients are on statin and aspirin as well as β-blockers and for CAS dual antiplatelet agents is mandatory. 15,16 Statins have been shown to be protective for mortality following CEA and CAS in previous studies; similarly in this study, statins have shown 71% reduction in mortality. 16,17 We patch all our CEA under EEG and evoked potential monitoring with selective shunting.…”
Section: Discussionsupporting
confidence: 81%
“…Obeid and colleagues found no link between beta-blocker therapy and stroke risk in patients preprocedurally treated with beta-blockers for more than 30 days. 38 This might be explained by the beta-blocker dose administered: in the POISE study patients received 200 mg extended-release metoprolol daily, 34 whereas the highest daily dose prescribed for patients in the current study was 125 mg metoprolol with the majority receiving a dose of 50 mg. Additionally, an overwhelming majority of beta-blocker exposed patients in the current study had received the drug for at least 12 months prior to surgery. This contrasts with the POISE trial where beta-blocker treated patients were drug-naïve up until drug-initiation immediately before surgery, suggesting that a period of Open access adjustment to the drug may be beneficial prior to the patient undergoing surgery.…”
Section: Open Accessmentioning
confidence: 88%
“…The negative effect of smoking gives credence to the need for vascular surgeons and interventionists to contribute actively to multidisciplinary efforts to help patients quit smoking. The avoidance of ballooning after stent deployment 29,30 and the use of b-blockers 31 have been shown to positively affect CAS outcomes in patients with de novo disease. These might also be useful in further improving outcomes after treatment of restenosis with CAS.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%